2021
DOI: 10.1080/1463922x.2021.1881653
|View full text |Cite
|
Sign up to set email alerts
|

Authority gradients between team workers in the rail environment: a critical research gap

Abstract: Communication errors feature prevalently as causal and contributory factors in accident analysis within rail. While matters of phraseology and protocol in communication have been used to categorise communication error, formal inquiries into major rail accidents point to an underlying "authority gradient" as an influencing factor. The aim of this paper was to understand how the influence of authority gradients on communication error has been explored by communities of research and practice in rail. To achieve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Inquiries into major rail accidents emphasise an underlying authority gradient as an influencing factor in communication errors that resulted in near misses and fatalities. 26 A recent review of 235 railway incidents in Great Britain revealed that 21% of accidents were identified with communication error and escalation failure as a contributing factor. 27 Similar themes are also highlighted in major maritime incidents, where advice from lower ranking officers has been ignored, leading to disaster.…”
Section: How Other High-risk Industries Create a Shallow Workplace Au...mentioning
confidence: 99%
“…Inquiries into major rail accidents emphasise an underlying authority gradient as an influencing factor in communication errors that resulted in near misses and fatalities. 26 A recent review of 235 railway incidents in Great Britain revealed that 21% of accidents were identified with communication error and escalation failure as a contributing factor. 27 Similar themes are also highlighted in major maritime incidents, where advice from lower ranking officers has been ignored, leading to disaster.…”
Section: How Other High-risk Industries Create a Shallow Workplace Au...mentioning
confidence: 99%
“…This is suggestive of a hierarchical cultural contribution to the generation of an authority gradient that warrants future research focus. As a key dimension of cultural relativity, power distance theory, devised by Hofstede (1983) and applied in similar systems such as aviation, is a relevant theoretical tool for providing further understanding on these relationships (Luva & Naweed 2021). Further research into team interdependencies with a focus on track worker and train crew groups and the cultural factors that serve to construct relationships across teams is a key direction for future research.…”
Section: Strengths Limitations and Future Research Directionsmentioning
confidence: 99%
“…They provide direction to other workers, which includes provision of authority to train drivers for rail vehicle movements, and track maintenance workers for access and length of time permitted on track (Baldry & Ellison 2006). These dynamics, while critical for safe working, also have potential to create an authority gradient between the network controller and other workers (Luva & Naweed 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work occurs in a potentially hazardous environment, where track workers need protection from nearby service or engineering trains [1,2]. It can take place in remote or difficult to access locations such as tunnels, at night and in poor weather [3][4][5] and requires complex communications that are prone to error [6]. It may also require physically demanding work such as the manual handling and mounting of catenary equipment [7,8].…”
Section: Introductionmentioning
confidence: 99%